(untitled) (Journal of Namibian Studies : History Politics Culture, 2023)
The impact of a student’s reading comprehension skills is the second crucial individual talent in the effectiveness of word problem solving. The objective of the study was to Measure 8th grade student’s working memory capacity, word problem solving ability, find out the relationship student’s working memory and word problem solving at 8th grade and find out the effect of demographic variables (gender, age and area) on student’s working memory and word problem solving ability. The population of this study was the male and female mathematics students of public schools of Lahore. Two measuring instruments were used for data collection about students working memory and word problem solving. Data analyses consisted of descriptive statistics. Cronbach’s alpha used to explain consistency of measuring instruments used in research. The findings of the study shoes that strong relationship between working memory and word problem solving at 8th grade.